The Position of the Constitutional Court in the Sphere of Judicial Power - Gusthomi, Moh. Imam; Widyawati, Anis; Ramadan, Daud Renata Candra; Wijayanti, Zulfa Rena; Islam, Adiba Ro'uf Danur (Indonesian Journal of Pancasila and Global Constitutionalism, 2024)
This study aims to find and analyze the Herarki or the position of the Constitutional Court in the Scope of Judicial power. Where the decisions issued by the constitutional court are binding for all legal subjects and final, which means that the first and last decisions cannot be appealed. So this research is important to be researched from the history of the idea of the emergence of the constitutional court and its position in the scope of judicial power. In this study, the author will examine the position of the constitutional court based on the 1945 Constitution of the Republic of Indonesia (1945 Constitution of the Republic of Indonesia) and positive norms that are still in force today (ius contitutum). Based on this description, this study focuses on two problem formulations, namely first, how historically the constitutional court was formed as an institution within the scope of judicial power. Second, what is the position of the constitutional court within the scope of judicial power? This research is a normative research with the main research methods used are the statute approach, historical approach and conceptual approach. In this study, it is drawn from the history of the emergence of the Constitutional Court Institution and entered as one of the spheres of judicial power. Where in the judicial power there are 3 institutions including the Supreme Court Institution, the Judicial Commission Institution and the Constitutional Court Institution. The position in the institution is aligned with no higher or highest institution. Institutions within the scope of judicial power have the principle of check and balance and are independent.